2020
DOI: 10.47540/ijsei.v1i3.60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Metals Emissions on Ecosystem of Pakistan

Abstract: Environmental contamination is one of the significant problems of modern society. Heavy metal pollutants include zinc, arsenic, nickel, cadmium, copper, lead, chromium, manganese, and iron etc. Their universal bioavailability accumulation in the food chain causes severe effects on human health. The lives of living species will be preserved by unique heavy metal treatments to improve the air, soil, and water quality. This review article represents a glimpse of heavy metal contamination in several areas of Pakis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…The highest Zn concentration in the bread samples analyzed was observed for sample AII (0.817mg/kg) while the lowest was in sample AIX (0.423mg/kg). These values are within the permissible level of Zn in foods (50mg/kg) (Asif, Sharf and Anwar 2020).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The highest Zn concentration in the bread samples analyzed was observed for sample AII (0.817mg/kg) while the lowest was in sample AIX (0.423mg/kg). These values are within the permissible level of Zn in foods (50mg/kg) (Asif, Sharf and Anwar 2020).…”
Section: Discussionsupporting
confidence: 61%
“…The concentration of Cu in the bread samples ranged from 0.04-0.18 mg/kg. These concentrations are within the permissible level of Cu in foods (Asif, Sharf and Anwar 2020).…”
Section: Discussionsupporting
confidence: 54%
“…Plants in the instantaneous vicinity of emissions sources are more susceptible. For the maturing season, at concentrations of about 1850 μg/m 3 for 1 h, 500 μg/m 3 for 8 h, and 40 μg/m 3 has been revealed that the most sensitive species of plants start on to show visible signs of spoil to sulfur oxides (Asif et al, 2020) In terms of foliar injury, biochemical alterations on vegetation and physiological sulfur dioxide show harmful effects, and short-term SO2 destroyed PSII, decreased the fluidity of the thylakoid membrane, and also affect the process of electron transport. The leaf is the most sensitive part of the air pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…Coal‐fired power plants are a major source of air pollution and greenhouse gas emissions. In addition to heavy metals such as carbon monoxide and mercury, charcoal releases sulphur dioxide, a toxic substance associated with acid rain (Asif et al ., 2020). In addition to heavy metals that include mercury, selenium, lead, and arsenic and the emission of greenhouse gases that leave harmful by‐products when coal is burned.…”
Section: Introductionmentioning
confidence: 99%